Serología positiva a Leptospira interrogans, serovar cynopteri en caninos de la Ciudad de Buenos Aires, Argentina - Tealdo, M.S. (2007)
Leptospirosis is an infectious illness caused by Leptospira bacteria which affects humans and domestic and wilds animals. It may live in rivers, streams, lakes, and ponds. The illness can have several clinical forms. Canines may be a human source of infection due to their close contact. Leptospira genus includes two species: L. interrogans (pathological), and L. biflexa (non pathological). These species are further divided in serogroups and serovars. Between June and September 2003, 110 samples were collected from canines treated in the (Instituto de Zoonosis Luis Pasteur (IZLP). The samples were analyzed in IZLP and Instituto de Patobiología, INTA, Castelar (Provincia de Buenos Aires), using the microagglutination Martin and Petit technique. Samples tested against 23 serovars resulted in 33% seroprevalence. Unexpectedly, the cinopteri serovar was found in 59% of positive samples. Out of the whole population (51% males and 49% females) of positive animals, 30% came from poor neighborhoods and ?slums? and 70% from the rest of the city. A number of factors may have changed in these last years due to the economic crisis (people working manipulating rubbish, the use of horses in the city and clandestine pig breed). Due to the increase in overall seroprevalence above the historical range and detection of the uncommonly tested cinopteri servovar in a large percentage of samples, it would be advisable to analyze more serovars in canine serological tests.